Effect of an E-learning resource on endoscopists’ proximal serrated polyp detection rate: a randomized controlled trial - van Toledo, David E. F. W. M.; IJspeert, Joep E. G.; Bleijenberg, Arne G. C.; Depla, Anne; Montazeri, Nahid S. M.; Dekker, Evelien (Endoscopy, 2024)
Background Recent studies demonstrated that a higher proximal serrated polyp detection rate (PSPDR) among endoscopists is associated with a lower risk of post-colonoscopy colorectal cancer (PCCRC) incidence and death for their patients. Our objective was to evaluate the effect of an e-learning resource on PSPDR.Methods We performed a multicenter randomized controlled trial within the Dutch fecal immunochemical test-based colorectal cancer screening program. Endoscopists were randomized using block randomization per center to either receive a 60-minute e-learning resource on serrated polyp detection or not. PSPDR was calculated based on all colonoscopies performed during a 27-month pre-intervention and a 17-month post-intervention period. The primary end point was difference in PSPDR between intervention and control arms (intention to treat) using mixed effect logistic regression modeling, with time (pre-intervention/post-intervention) and interaction between time and arm (intervention/control) as fixed effects, and endoscopists as random effects.Results 116 endoscopists (57 intervention, 59 controls) were included, and performed 27494 and 33888 colonoscopies, respectively. Median PSPDR pre-intervention was 13.6% (95%CI 13.0–14.1) in the intervention arm and 13.8% (95%CI 13.3–14.3) in controls. Post-intervention PSPDR was significantly higher over time in the intervention arm than in controls (17.1% vs. 15.4%, P=0.01).Conclusion In an era of increased awareness and increasing PSPDRs, endoscopists who undertook a one-time e-learning course significantly accelerated the increase in PSPDR compared with endoscopists who did not undertake the e-learning. Widespread implementation might reduce PCCRC incidence.